Society of Anesthesia and Sleep Medicine Guideline on Intraoperative Management of Adult Patients With Obstructive Sleep Apnea. (October 2018) - Memtsoudis, Stavros G.; Cozowicz, Crispiana; Nagappa, Mahesh; Wong, Jean; Joshi, Girish P.; Wong, David T.; Doufas, Anthony G.; Yilmaz, Meltem; Stein, Mark H.; Krajewski, Megan L.; Singh, Mandeep; Pichler, Lukas; et al.
Abstract : The purpose of the Society of Anesthesia and Sleep Medicine Guideline on Intraoperative Management of Adult Patients With Obstructive Sleep Apnea (OSA) is to present recommendations based on current scientific evidence. This guideline seeks to address questions regarding the intraoperative care of patients with OSA, including airway management, anesthetic drug and agent effects, and choice of anesthesia type. Given the paucity of high-quality studies with regard to study design and execution in this perioperative field, recommendations were to a large part developed by subject-matter experts through consensus processes, taking into account the current scientific knowledge base and quality of evidence. This guideline may not be suitable for all clinical settings and patients and is not intended to define standards of care or absolute requirements for patient care; thus, assessment of appropriateness should be made on an individualized basis. Adherence to this guideline cannot guarantee successful outcomes, but recommendations should rather aid health care professionals and institutions to formulate plans and develop protocols for the improvement of the perioperative care of patients with OSA, considering patient-related factors, interventions, and resource availability. Given the groundwork of a comprehensive systematic literature review, these recommendations reflect the current state of knowledge and its interpretation by a group of experts at the time of publication. While periodic reevaluations of literature are needed, novel scientific evidence between updates should be taken into account. Deviations in practice from the guideline may be justifiable and should not be interpreted as a basis for claims of negligence.